Grammatical Category of Nepali and Doteli Language - Singh , Karishma (Academia Research Journal, 2023)
The problem statement of the study is to identify the grammatical categories (gender, person, aspect, voice, mood, case, respect, and tense) in Doteli and Nepali languages. On the basis of their similarity and difference, the purpose is to solve the possible problems in teaching and learning. This is a qualitative research design based on purposive sampling. The primary participants (A and B) of this study are two native speakers of Doteli who are from the Kailali district, Nepal. The interview was held based on structured questions. Further data was collected from books and other published resources. The collected data were analysed on the basis of similarities and differences between those two languages. It was concluded that there is a possible chance to commit errors Doteli first language speakers to learn Nepali as the second language. It is believed that this study will be useful to those who want to carry out study in grammatical categories.